2016
DOI: 10.1007/s10648-016-9361-7
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Cognitive Scaffolding with Computer-Supported Collaboration Scripts: a Meta-Analysis

Abstract: Scripts for computer-supported collaborative learning (CSCL) offer socio-cognitive scaffolding for learners to engage in collaborative activities that are considered beneficial for learning. Yet, CSCL scripts are often criticized for hampering naturally emerging collaboration. Research on the effectiveness of CSCL scripts has shown divergent results. This article reports a meta-analysis about the effects of CSCL scripts on domain-specific knowledge and collaboration skills. Results indicate that CSCL scripts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
102
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(110 citation statements)
references
References 59 publications
2
102
0
6
Order By: Relevance
“…These collaborators will experience less cognitive load and better knowledge structures due to task related transactive activities. A recent meta-analysis provides evidence that CSCL scripts substantially improve learning outcomes for domain-specific knowledge and collaborative skills compared to unstructured CSCL (Vogel et al 2016).…”
Section: Collaborative Learning and Evolutionary Categories Of Knowledgementioning
confidence: 99%
“…These collaborators will experience less cognitive load and better knowledge structures due to task related transactive activities. A recent meta-analysis provides evidence that CSCL scripts substantially improve learning outcomes for domain-specific knowledge and collaborative skills compared to unstructured CSCL (Vogel et al 2016).…”
Section: Collaborative Learning and Evolutionary Categories Of Knowledgementioning
confidence: 99%
“…The scene component has to do with knowledge about situations that may follow each other within the play. For example, during CABLe, a possible scene could be the initial individual idea generation by different learners or the joint development of a solution for the issue at stake (Fischer et al 2013;Kollar et al 2014;Vogel et al 2016).…”
Section: Determining the Learner's Internal Argumentative Scriptmentioning
confidence: 99%
“…For example, in a particular scene, for responding to analysis, a learner's internal script may include scriptlets suggesting to first read the analysis of the learning partner, to evaluate the analysis, and then provide counterarguments to that analysis (see Fischer et al 2013;Kollar et al 2014). Detailed information on the SToG with examples from a range of different studies can be found in Fischer et al (2013), Kirschner and Erkens (2013), Kollar et al (2014), andVogel et al (2016).…”
Section: Determining the Learner's Internal Argumentative Scriptmentioning
confidence: 99%
“…However, scholars have reported that not all students could harness the potentials of CSCL environments [16,17]. Indeed, in contrast to the positive findings, there is also a vast body of research literature reporting mixed or negative findings [18,19]. Scholars assert that given the nature of CSCL (i.e., technological and collaborative dependence, high level of agency, and autonomy), an inadequate level of students' readiness for CSCL is one of the important reasons for such discrepancy in terms of mixed positive and negative findings [20,21].…”
Section: Introductionmentioning
confidence: 99%